Detection of Fusobacterium nucleatum in culture-negative brain abscess by broad-spectrum bacterial 16S rRNA Gene PCR. (2017) - Chakvetadze, Catherine; Purcarea, Anastasia; Pitsch, Aurelia; Chelly, Jonathan; Diamantis, Sylvain
Abstract: Background: Fusobacterium nucleatum is a strict anaerobic microorganism commensal to the human oropharynx and gastrointestinal tract, which causes a wide spectrum of human diseases and it is an important pathogen in abscesses. Case presentation: We report the case of a previously healthy 64-year-old woman with multiple abscesses due to Fusobacterium nucleatum, involving liver, pleura and brain. Fusobacterium was not recovered from blood cultures nor from culture of hepatic, pleural and brain drain fluid. The diagnosis was obtained by polymerase chain reaction amplification of bacterial deoxyribonucleic acid in brain abscess drain. Conclusions: Fusobacterium spp., should be considered in patients with any organ abscess, especially in case of invasive disease with multiple secondary site involving brain. Molecular: techniques might be of special usefulness in cases that remain negative in culture to obtain the diagnosis and perform adequate treatment.